Risks of artificial intelligence - Muller, Vincent C. (CRC Press, 2016)
If the intelligence of artificial systems were to surpass that of humans, humanity would face significant risks. The time has come to consider these issues, and this consideration must include progress in artificial intelligence (AI) as much as insights from AI theory.
CRIS-Team Scopus Importer:2023-03-08